KEANEKARAGAMAN SPESIES BACTROCERA DAN PARASITOIDNYA YANG MENYERANG BERBAGAI JENIS BUAH DI PASAR BANDUNGAN - DYAH RINI INDRIYANTI; DUHITA ENDRAWILA PINASTHIKA; BAMBANG PRIYONO (JURNAL ILMIAH AGRINECA, 2014)
Bactrocera fruit flies are important pests which attack many kinds of fruit. The aims of this study were identifying the diversity index and parasitoid of Bactrocera in some fruits attacked in Bandungan Market, Semarang Regency. The are eight kinds of fruit used in this study ie; mango, guava, rose-apple, star fruit, peppers, jackfruit, oranges, and tomatoes. Rotten fruit were brought to the laboratory, Bactrocera were reared until imago and examined the diversity of species and the parasitoids. Five types of them are positive containing  Bactrocera  inside the fruit; mango, guava, rose-apple, and star fruit. There are two species of Bactrocera found, they are Bactrocera carambolae and Bactrocera papaye. The level of diversity of fruit flies was low  (0,11). Bactrocera carambolae  more dominan than Bactrocera papaye. The Bactrocera composition similarity was 75%. Parasitoids found  in this study are Fopius arisanus and Opius dichasmimorpha.